Freshwater Aquaculture Development Strategty At Kao Barat And Tobelo North Halmahera Regency - Sophia N M Fendjalang (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The Aim of this research was to describe the profile of freshwater aquaculture, identify external and internal factors and formulate a strategy for developing freshwater aquaculture. The research was conducted at freshwater aquaculture locations in West Kao and Tobelo. The method used purposive sampling methods, observation, and interviews, data analysis used qualitative descriptive methods and SWOT. The results showed that human resources and skills in cultivating fish, availability of land, water sources and locations, the existence of Balai Benih Ikan Lokal are strength factors, while capital and experience, quality and quantity of seeds are weaknesses that affect the development of freshwater aquaculture. On the other hand, threats such as the lack of government guidance and assistance, weather, location security are obstacles in taking advantage of opportunities consisting of opening employment opportunities, developing cultivation technology including Minapadi, selling prices, and marketing. The strategies used to formulate the development of freshwater aquaculture in West Kao and Tobelo are increasing the role of the government through outreach activities, increasing the quality and quantity of fish cultured by BBIL, developing an integrated aquaculture system, improving the safety system of aquaculture sites and increasing knowledge about hatchery techniques to cultivators.